Implementasi Kebijakan Percepatan Pemulihan Ketahanan Ekonomi dan Kehidupan Masyarakat Dimasa Pandemi Covid-19 di Kecamatan Medan Deli Kota Medan - Muhammad Ardian; Arief Marizki Purba (PERSPEKTIF, 2022)
This research aims to describe how the implementation of the policy to accelerate economic recovery and people's lives during the covid-19 pandemic in Medan Deli District and analyze the Supporting and Inhibiting Factors. The method used is descriptive research method with a qualitative approach. In-depth interviews with various stakeholders in the policy. The analysis was carried out qualitatively. The results of this study indicate that the implementation of the Policy for the Acceleration of Recovery of Economic Resilience and Community Life during the Covid-19 Pandemic in the Medan Deli District has been going quite well. The whole series or process of activities starting from initial socialization, poverty reflection, program implementation, program monitoring all went quite well. The success of the Policy to Accelerate the Recovery of Economic Resilience and Community Life During the Covid-19 Pandemic is strongly supported by the effectiveness of implementing organizations in providing learning, mentoring, independence, for underprivileged communities affected by the COVID-19 pandemic. The obstacle that occurs in the implementation of this policy is that there are still people who should be entitled to benefit from this policy program, do not receive social assistance, this is because they are not recorded in the list of beneficiaries. The weak data collection carried out has caused some problems in the distribution of social assistance.